Pengaruh Kedisiplinan Dosen terhadap Motivasi Belajar Mahasiswa Fakultas Tarbiyah di STAI Balikpapan - Syafi’i, Muhammad Abdulloh; Yusuf, Iskandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of lecturer discipline on student learning motivation of Tarbiyah faculty at Balikpapan Islamic Religious College. This research uses quantitative approach with a sample of 40 students from a population of 100 active students. Data were collected through questionnaire using Likert scale. The data obtained from the research were processed using simple regression analysis. Based on the result of the research, it can be concluded that there is a significant influence between lecturer's discipline (X) to students' learning motivation (Y). These results can be seen through the t test results obtained a probability value of (0.002). This value is smaller than 0.05, so it can be concluded that there is a significant influence between lecturer discipline and learning motivation.